Obesity is the basis of metabolic syndrome - A. F. Verbovoy; N. I. Verbovaya; Yu. A. Dolgikh (Ожирение и метаболизм, 2021)
Metabolic syndrome is a symptom complex that is based on visceral obesity and insulin resistance. Its prevalence is quite high, which is a big problem, since this condition increases the risk of developing cardiovascular diseases and mortality from them. Metabolic syndrome includes, in addition to abdominal obesity, arterial hypertension, disorders of carbohydrate, lipid and purine metabolism. Visceral adipose tissue plays a key role in the formation of insulin resistance and other components of the metabolic syndrome. This is due to the fact that abdominal fat, in contrast to subcutaneous fat, synthesizes pro-inflammatory cytokines, as well as adipokines — adipose tissue hormones that are involved in the formation of insulin resistance, affect carbohydrate and fat metabolism and the cardiovascular system. These include leptin, adiponectin, resistin, apelin and others. Some adipokines have an adverse effect on metabolism and increase cardiovascular risks, while others, on the contrary, have a positive effect. Taking into account their role in the development of the components of the metabolic syndrome, the possibilities of a therapeutic effect on the hormones of adipose tissue to improve metabolic processes and prevent complications associated with it are discussed.